Prevalence of Posttraumatic Stress Disorder (PTSD) among the Iraqi Repatriated Prisoners of the Iran-Iraq War, 1980-1988 - Al-Ameri, maan; gee, Ivan; Ma’ala, iqbal; Wallymahmed, Akhtar (Iraqi National Journal of Nursing Specialties, 2015)
Objective: To determine the prevalence of Posttraumatic Stress Disorder (PTSD) among Iraqi repatriated prisoners of Iran-Iraq war, and the relationship with demographic factors. Methodology: A descriptive study was carried out from Oct. 18th, 2009 through Jan. 10th, 2010. A nonprobability based snowball sampling technique was used to recruit 92 Iraqi repatriated prisoners of war (IRPOWs) who had visited Ministry of Human Rights. A data collection instrument was constructed that consisted of six demographic characteristics, and eight items to measure the level of PTSD in POWs. Data were collected with the constructed instrument during a brief interview. Data were analyzed through the application of descriptive statistical analysis: percentages; frequencies and inferential statistic analysis (Pearson correlation coefficient). Results: The study revealed that the majority of IRPOWs have some level of PTSD (78.3%). Proportions of IRPOWs with low, medium and high severity PTSD: Low (29.3%); medium (32.6%) and high (16.4%). Statistically significant relationships were observed between PTSD and duration of captivity, marital status and level of education. Recommendations: The study recommends special mental health services centres are established within primary health care centres in order to diagnose and treat them and that further studies are conducted to explore effective treatments for IRPOWs